1997
DOI: 10.2307/2329480
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at the Monday Effect

Abstract: It is well documented that expected stock returns vary with the day-of-the-week (the Monday or weekend effect). In this article we show that the well-known Monday effect occurs primarily in the last two weeks (fourth and fifth weeks) of the month. In addition, the mean Monday return of the first three weeks of the month is not significantly different from zero. This result holds for most of the subperiods during the 1962-1993 sampling period and for various stock return indexes. The monthly effect reported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
5
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 4 publications
12
75
5
3
Order By: Relevance
“…There are number of studies which have supported the Monday effect in the stock markets (Alt et al, 2011;Cho et al, 2007;Jaffe et al, 1989). However, other studies support the ef icient market hypothesis and are not in line with the Monday effect (Bhana, 1985;Diaconasu et al, 2012;Mehdian and Perry, 2001;Wang et al, 1997). Also, Ajayi et al (2004) Seyyed et al (2005) found the existence of Ramadan effect in Saudi Arabia.…”
Section: Monday Effectmentioning
confidence: 86%
“…There are number of studies which have supported the Monday effect in the stock markets (Alt et al, 2011;Cho et al, 2007;Jaffe et al, 1989). However, other studies support the ef icient market hypothesis and are not in line with the Monday effect (Bhana, 1985;Diaconasu et al, 2012;Mehdian and Perry, 2001;Wang et al, 1997). Also, Ajayi et al (2004) Seyyed et al (2005) found the existence of Ramadan effect in Saudi Arabia.…”
Section: Monday Effectmentioning
confidence: 86%
“…Then, researchers interested in this kind of anomaly in their turns applied a strategy derived from Ariel's findings to make more clear that stock market returns are generally higher on the last day of the month and the first days of the next month. More precisely, the returns during the first week of a month tend to be significantly positive, while the returns during the other weeks of a month are statistically indistinguishable from zero (Wang et al, 1997;Kohers and Patel, 1999).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Moreover, authors Wang, Li and Erickson (1997) distinguish between days of the first and of the latter half of the month. They consider that the day-of-the-week effect on the stock return changes according to whether the day comes in the first or the latter half of the month.…”
Section: The Day-of-the-week Effect On Return and Trading Volumementioning
confidence: 99%